Proteasome subunit expression analysis and chemosensitivity in relapsed paediatric acute leukaemia patients receiving bortezomib-containing chemotherapy. Issue 1 (December 2016) - Niewerth, Denise; Kaspers, Gertjan; Jansen, Gerrit; van Meerloo, Johan; Zweegman, Sonja; Jenkins, Gaye; Whitlock, James; Hunger, Stephen; Lu, Xiaomin; Alonzo, Todd; van de Ven, Peter; Horton, Terzah; et al.
Abstract Background Drug combinations of the proteasome inhibitor bortezomib with cytotoxic chemotherapy are currently evaluated in phase 2 and 3 trials for the treatment of paediatric acute myeloid leukaemia (AML) and acute lymphocytic leukaemia (ALL). Methods We investigated whether expression ratios of immunoproteasome to constitutive proteasome in leukaemic cells correlated with response to bortezomib-containing re-induction chemotherapy in patients with relapsed and refractory acute leukaemia, enrolled in two Children's Oncology Group phase 2 trials of bortezomib for ALL (COG-AALL07P1) and AML (COG-AAML07P1). Expression of proteasome subunits was examined in 72 patient samples (ALLn  = 60, AMLn  = 12) obtained before start of therapy. Statistical significance between groups was determined by Mann-WhitneyU test. Results Ratios of immunoproteasome to constitutive proteasome subunit expression were significantly higher in pre-B ALL cells than in AML cells for both β5i/β5 and β1i/β1 subunits (p  = 0.004 andp  < 0.001). These ratios correlated with therapy response in AML patients; β1i/β1 ratios were significantly higher (p  = 0.028) between patients who did (n  = 4) and did not reach complete remission (CR) (n  = 8), although for β5i/β5 ratios, this did not reach significance. For ALL patients, the subunit ratios were also higher for patients who showed a good early response to therapy but this relation was not statistically significant. Overall, for this study, the patients were treated with combination therapy, so response was not only attributed to proteasome inhibition. Moreover, the leukaemic blast cells were not purified for these samples. Conclusions These first ex vivo results encourage further studies into relative proteasome subunit expression to improve proteasome inhibition-containing therapy and as a potential indicator of bortezomib response in acute leukaemia.